2013
DOI: 10.1017/s1742058x1300012x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Group Threat and Malleable White Attitudes Towards Academic Merit

Abstract: As the White populace in the United States moves toward numerical minority status by 2042, how might Whites respond to impending threat of losing their dominant group position? In particular, how will Whites react at selective, elite universities, where Asians are increasingly prominent and other non-Whites are maintaining or capturing a larger share of enrollments? Drawing on group position theory, I test White commitment to meritocracy as a public policy, using a survey-based experiment (599 California adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 51 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…With the advent of holistic notions of merit, Asian Americans are particularly susceptible to stereotypes and being held to a higher standard of excellence than other racial and ethnic groups, particularly on nonstandardized measures of achievement such as leadership and cocurricular activities (Park & Liu, ). The perception of “group threat” by Asian American students in the admissions process was confirmed in a study conducted by Frank Samson that highlights the fluidity in public perceptions of meritocracy (Samson, ). When one group of White adults in California was asked about the criteria that should be used in admissions processes, a high priority was placed on high school grade‐point averages and standardized tests.…”
Section: The Changing Paradigm: Access and Success Of Minoritized Stumentioning
confidence: 84%
“…With the advent of holistic notions of merit, Asian Americans are particularly susceptible to stereotypes and being held to a higher standard of excellence than other racial and ethnic groups, particularly on nonstandardized measures of achievement such as leadership and cocurricular activities (Park & Liu, ). The perception of “group threat” by Asian American students in the admissions process was confirmed in a study conducted by Frank Samson that highlights the fluidity in public perceptions of meritocracy (Samson, ). When one group of White adults in California was asked about the criteria that should be used in admissions processes, a high priority was placed on high school grade‐point averages and standardized tests.…”
Section: The Changing Paradigm: Access and Success Of Minoritized Stumentioning
confidence: 84%
“…This study shows that when group threat to valued resources was activated, students supported unequal standards that favored white students over Asian American students. Similarly, a study of California residents found white respondents minimized the importance of Grade Point Average for college admissions when group threat from Asian Americans was activated, but increased its importance when threat from only African Americans or both African Americans and Asian Americans was activated (Samson, ). This research shows support for Group Position Theory in relation to Asian Americans in education, but has not been tested related to Asian Americans in jobs.…”
Section: Group Position Theorymentioning
confidence: 99%
“…Fewer studies use Group Position Theory to understand the social position of Asian Americans in relation to other groups in the United States. Exceptions include studies using Group Position Theory to understand Asian Americans’ attitudes toward public policies and other racial/ethnic groups (Inkelas, ) and whites’ attitudes toward Asian Americans in college admissions (Samson, , ). Pertinent to this study and consistent with Group Position Theory, survey research shows that whites feel a heightened sense of competition with Asian Americans relative to other minority groups in various contexts, including the workforce (Bobo and Hutchings, ; Hutchings et al., ).…”
mentioning
confidence: 99%
“…in a compelling example, a recent study found that White adults are more likely to support flexible, holistic versions of merit when they are reminded that asian americans in the Uc system make up more than double their proportional representation in the state of california. however, when they were simply asked about criteria for Uc admission without any mention of asian americans, they favored a heavier emphasis on standardized tests and Gpa in admissions (Samson, 2013;Jaschik, 2013).…”
Section: (Re)defining Meritocracy: the Need For More Holistic Definitmentioning
confidence: 99%